PRODUCTION DEVELOPMENT OF GRP PERAHU KOLEK - Nur Ain, A.R; Mohd Azahari, J.; Khairuddin, N.M.; Norhanifah, A.R; N. Manap; Hanipah Ghazali (Marine Frontier, 2023)
Perahu Kolek is a traditional Malaysian boat building made of wood and is usually used in coastal areas. The design and fabrication of wooden Kolek required a high level of workmanship and skills, and most of the process was done manually by skilled workers. This results in a high production cost of material, labor cost, and production time. Glass-reinforced plastic (GRP) is used in the production of modern hull boats as it has several advantages, for example, being a cheaper, stronger, and waterproof material. Generally, the fabrication of the modern fiberglass boat starts with the construction of the hull boat plug, followed by the mould fabrication, and finishes with the production of the boat using fiberglass. In this project, the simplified development of GRP Kolek hull mould using Computer Aided Manufacturing (CAM) using Rhinoceros software, Power Mill software, and application of 5-axis Computer Numerical Control (CNC) machining will be discussed. The Kolek hull plug process is required in order to produce a hull mould. Somehow, in this production process, it directly produces the hull mould using a 5-axis Computer Numerical Control (CNC) machine. Then, the fabricated mould made of foam will be used for GRP Kolek production. The result of this new technology development can be used as an aid to the new material and concept, high quality and cost saving traditional boats at the same time supporting the preservation of traditional boat building.